Strategi Komunikasi Pemasaran Digital Untuk Meningkatkan Customer Engagement UMKM (Studi Kasus Bubur Ayam Bang One Medan Johor Tahun 2025) - Rizky Amanda Putri; Abdul Rasyid (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
Small and Medium Enterprises (SMEs) have a strategic role in driving local economic growth and increasing the competitiveness of the informal sector. This study aims to analyze the digital marketing communication strategy implemented by SMEs Bubur Ayam Bang One in Medan Johor in increasing customer engagement during 2024. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews with owners, sellers, and customers, as well as observations of digital content activities uploaded through various social media platforms. The results of the study show that the use of digital platforms such as TikTok, Instagram, WhatsApp, and food delivery services can expand market reach and increase customer interaction. The main strategies implemented include collaboration with local influencers, utilizing viral trends, and compiling emotionally attractive visual content. Supporting factors include customer enthusiasm and TikTok usage trends, while obstacles faced include limited promotional budgets and high business competition. This study recommends that SMEs optimize creative content and strengthen digital community engagement as part of a long-term strategy to maintain customer loyalty and increase business desire.